2021
DOI: 10.2147/ijn.s344318
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Oleoylethanolamide Crystals Loaded Lipid Nanoparticles with Enhanced Hydrophobic Drug Loading Capacity for Efficient Stroke Therapy

Abstract: Introduction:Although the preparation of lipid nanoparticles (LNPs) achieves great success, their retention of highly hydrophobic drugs is still problematic. Methods: Herein, we report a novel strategy for efficiently loading hydrophobic drugs to LNPs for stroke therapy. Oleoylethanolamide (OEA), an endogenous highly hydrophobic molecule with outstanding neuroprotective effect, was successfully loaded to OEA-SPC&DSPE-PEG lipid nanoparticles (OSDP LNPs) with a drug loading of 15.9 ± 1.2 wt %. Efficient retentio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Wu et al reported a novel preparation method for efficiently loading hydrophobic drugs (endogenous high hydrophobic molecular oil ethanolamide with significant neuroprotective effects) to liposome for stroke treatment (Wu et al, 2021). The effective retention of oleoylethanolamide (OEA) in liposome could significantly enhance neuroprotective effects.…”
Section: Liposomementioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al reported a novel preparation method for efficiently loading hydrophobic drugs (endogenous high hydrophobic molecular oil ethanolamide with significant neuroprotective effects) to liposome for stroke treatment (Wu et al, 2021). The effective retention of oleoylethanolamide (OEA) in liposome could significantly enhance neuroprotective effects.…”
Section: Liposomementioning
confidence: 99%
“…The effective retention of oleoylethanolamide (OEA) in liposome could significantly enhance neuroprotective effects. Liposome could significantly improve the survival rate, behavior score, cerebral infarction volume, edema degree and spatial learning and memory ability of MCAO model rats (Wu et al, 2021). Resveratrol (NR), found in grapes and red wine, has good antioxidant and anti-inflammatory properties (Malaguarnera, 2019).…”
Section: Liposomementioning
confidence: 99%
“…The DLS result indicated that the OEA Liposomes possessed a hydrodynamic size of 97.6 ± 4.8 nm and a PDI of 0.193 ( Figure 2A ). Since the retention of highly hydrophobic drugs in liposomes was always problematic ( Zhigaltsev et al, 2010 ; Wu et al, 2021 ), the drug loading and loading efficiency of highly hydrophobic OEA was relatively low. The drug loading of OEA in the liposomes was 3.32% ± 0.46%.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, encapsulating OEA in a nanoparticulate structure like cubosomes, which may be utilized to target the BBB, protects it from hydrolysis and allows therapeutic amounts to reach the brain [ 36 ]. Another study by Wu et al showed that the survival rate, behavioral score, cerebral infarct volume, edema degree, spatial learning, and memory capacity of stroke-model rats could all be improved greatly using endogenous OEA crystals loaded lipid nanoparticles [ 37 ]. Further studies should be done in order to find the most effective format for OEA administration.…”
Section: Discussionmentioning
confidence: 99%